A numerical study of dendrite growth and microstructure transition in a non-equilibrium solidification. Issue 1 (May 2021) - Ao, Xiaohuia; Xia, Huanxiong; Liu, Jianhua; He, QiYang; Lin, Shengxiang
Abstract: Controlling the thermal condition of a solidification process to obtain a desirable microstructure morphology and then prepare specific materials with excellent mechanical properties or special functions has been attracting many concerns, where the behavior of microstructure morphology transition, especially the columnar-to-equiaxed transition, is one of the most important fundamental issues. This paper introduced a kinetic model for dendrite growth with a large undercooling during a non-equilibrium solidification process using cellular automaton, in which the local thermodynamic equilibrium condition, non-equilibrium partitioned solute, curvature and interface energy anisotropy were considered. The growth rate of dendrite tip was numerically investigated by using the cellular automaton model, and the effects of temperature gradient and cooling rate on the growth rate and morphology features were found. By integrating the simulation results and analytical models, a new microstructure morphology transition criterion for the non-equilibrium solidification depending on the temperature gradient and cooling rate was proposed, in which both the planar-to-columnar and the columnar-to-equiaxed transition were presented.